2013
DOI: 10.1016/j.bpj.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Membrane-Associated State of the PTEN Tumor Suppressor Protein

Abstract: Phosphatase and tensin-homolog deleted on chromosome 10 (PTEN) is a tumor-suppressor protein that regulates phosphatidylinositol 3-kinase (PI3-K) signaling by binding to the plasma membrane and hydrolyzing the 3' phosphate from phosphatidylinositol (3,4,5)-trisphosphate (PI(3,4,5)P3) to form phosphatidylinositol (4,5)-bisphosphate (PI(4,5)P2). Several loss-of-function mutations in PTEN that impair lipid phosphatase activity and membrane binding are oncogenic, leading to the development of a variety of cancers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 54 publications
8
55
0
Order By: Relevance
“…If this assumption is applied to PTEN, then the number of bound PI (4,5)P 2 molecules will be estimated as 3 or 4 when PTEN adopts the slower mobility state on the 10 mol% PI(4,5)P 2 membrane (D = 1.5 μm 2 s −1 ). Consistently, previous studies reported that R47 and K11/K13/R14/R15 possibly form two distinct sites for PI (4,5)P 2 binding, with K13 shared by both 18,35 . In addition, our results show that both R47A and N4 mutations cause a loss of the slower mobility state, possibly due to the reduction in the number of bound PI(4,5)P 2 molecules (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…If this assumption is applied to PTEN, then the number of bound PI (4,5)P 2 molecules will be estimated as 3 or 4 when PTEN adopts the slower mobility state on the 10 mol% PI(4,5)P 2 membrane (D = 1.5 μm 2 s −1 ). Consistently, previous studies reported that R47 and K11/K13/R14/R15 possibly form two distinct sites for PI (4,5)P 2 binding, with K13 shared by both 18,35 . In addition, our results show that both R47A and N4 mutations cause a loss of the slower mobility state, possibly due to the reduction in the number of bound PI(4,5)P 2 molecules (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…[12][13][14][15] PTEN contains a phosphatase domain in the N-terminal, a C2 domain and a C-terminal tail with 50 amino acids. [16][17][18] Each domain exhibits a certain function in relation to the membrane translocation of PTEN. 17 Binding of thioredoxin-1 to PTEN through a disulphide bond between the active site Cys32 of thioredoxin-1 and Cys212 of the C2 domain of PTEN inhibits PTEN membrane translocation and activation.…”
Section: Introductionmentioning
confidence: 99%
“…One powerful simulation technique that has the potential to yield atomically detailed information on Ras membrane binding and assembly is molecular dynamics (MD), particularly coarse-grained MD (CG-MD). CG-MD has been successfully used to study protein-lipid assemblies in large spatiotemporal scales [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41]. Applying CG-MD simulations on the minimal membrane-binding motif of H-Ras (tH), we have recently shown that 30–40% of these molecules spontaneously assemble into dynamic clusters of size 4–11 [42], [43].…”
Section: Introductionmentioning
confidence: 99%